Pharmacokinetics, safety, and tolerability of edoxaban in end-stage renal disease subjects undergoing haemodialysis - Parasrampuria, Dolly A.; Marbury, Thomas; Matsushima, Nobuko; Chen, Shuquan; Wickremasingha, Prachi K.; He, Ling; Dishy, Victor; Brown, Karen S. (Thrombosis and Haemostasis, 2015)
Edoxaban is an oral, direct, once-daily, factor Xa inhibitor developed for stroke prevention in patients with atrial fibrillation and for the treatment and secondary prevention of recurrent thromboembolism in patients with acute symptomatic venous thromboembolism. Among elderly patients who require anticoagulation therapies, some may have end-stage renal disease (ESRD). This open-label, phase 1, randomised, two-way crossover study was conducted to evaluate the pharmacokinetics of edoxaban in 10 subjects on haemodialysis. Eligible subjects with ESRD on chronic haemodialysis received a single, oraldose of edoxaban 15 mg 2 hours (h) prior to (on-dialysis) or in between (off-dialysis) haemodialysis sessions. Haemodialysis resulted in a minor decrease in mean total exposure (AUC0-∞; 676.2 ng⋅h/ml) as compared with that observed in subjects off-dialysis (691.7 ng⋅h/ml). Mean maximum observed plasma concentration (Cmax) values were comparable between on-dialysis and off-dialysis treatments (53.3 vs 56.3 ng/ml, respectively). Mean apparent total body clearance (CL/F) values were 24.1 and 22.5 l/h during the on-dialysis and off-dialysis treatment periods, respectively. Dialyser clearance was 5.7 l/h and haemodialysis clearance was 6.1 l/h. Haemodialysis clearance was only 6.1 l/h, suggesting that it only accounts for one-fourth of the total clearance in these subjects. A single, oral dose of 15 mg of edoxaban was well tolerated by subjects with ESRD. In conclusion, based on these single-dose PK data, a supplementary dose of edoxaban may not be required following a haemodialysis session. Importantly, haemodialysis is not an effective mechanism for removal of edoxaban from the blood.
Keywords: Edoxaban; haemodialysis; pharmacokinetics; oral factor Xa inhibitor; elimination